Ответ:
Пошаговое объяснение:
1.
![\left \{ {{x-y=1} \atop {x+y=7}} \right. \left \{ {{x-y=1} \atop {x+y=7}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx-y%3D1%7D%20%5Catop%20%7Bx%2By%3D7%7D%7D%20%5Cright.)
х - у + х + у = 1 + 7
2х = 8
х = 4
..................................
4 - у = 1 (домножим на (-1))
у - 4 = -1
у = 3
Ответ: (4;3)
2.
![\left \{ {3x - 8y = 18} \atop {-3x + 4y = -6}} \right. \left \{ {3x - 8y = 18} \atop {-3x + 4y = -6}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B3x%20-%208y%20%3D%2018%7D%20%5Catop%20%7B-3x%20%2B%204y%20%3D%20-6%7D%7D%20%5Cright.)
3х - 8у - 3х + 4у = 18 - 6
-4у = 12
у = -3
..................................
3х - 8*(-3) = 18
3х - (-24) = 18
3х + 24 = 18
3х = 18-24
3х = -6
х = -2
Ответ: ( -2; -3)